Differentiating characteristics among three new goat populations from northern India - SINGH, KARAN VEER; DIXIT, S P; SHARMA, ANURODH; VOHRA, VIKAS; KANT, NEEL; DANGI, P S; KUMAR, RAMESH (The Indian Journal of Animal Sciences, 2019)
Three non-descript goat populations, viz. Kumaoni and Garhwali of Uttarakhand hills, and Rohilkhandi of upper Ganges alluvial plain of Uttar Pradesh (India) were characterized phenotypically with standard morphometric parameters. The animals were also evaluated for their reproductive and production performance. The null hypothesis that Garhwali, Kumaoni and Rohilkhandi goat populations are same was tested using value of discriminant functions (D), Wilks’ Lambda and Box’s M statistics. The classification results revealed that 84.9% of all the goats were correctly classified to their own population. This could be used by livestock development agencies to take up appropriate breeding program for the improvement of native stock for future genetic conservation. The milk composition of Uttarakhand goats did not differ much due to geographic identities except for milk fat percentage. The study revealed that body height, body length, horn pattern, face length, and chest girth were the most discriminating and unique variables to separate Rohilkhandi, Kumaoni and Garhwali goat populations.